Iraq : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper discusses the choice and design of rules for Iraq, guided by fiscal policy priorities and the country's institutional capacity. A ceiling on current spending is proposed as a fiscal rule that would be simple and easy to monitor and support efforts to create space for scaling up capital expenditure, build fiscal buffers to reduce fiscal policy procyclicality, and help secure debt sustainability. A strong policy framework can help Iraq manage the challenges arising from its heavy dependence on volatile oil revenues. The procyclicality of fiscal policy has led to short-term economic volatility and hindered long term development. Important fiscal institutions such as fiscal rules, stabilization funds, and fiscal responsibility laws that exist in many resource-rich countries are lacking in Iraq. Moving to a risk- and rules-based approach can be part of the new policy framework and would be timely. The two main building blocks of this approach involve anchoring fiscal policy on maintaining adequate fiscal buffers, and introducing operational fiscal rules designed to achieve this target for buffers and protect capital expenditure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet